Response Analysis and Auto-Regressive Exogenous Modeling of a Steel-Reinforced Concrete High-Rise Building during the 2011 Off the Pacific Coast of Tohoku Earthquake - Nakamura, Naohiro; Kinoshita, Takuya; Fukuyama, Hiroshi (Frontiers in Built Environment, 2017)
Many seismic records were obtained during the 2011 off the Pacific coast of Tohoku earthquake. These records can be used to improve the seismic design and disaster prevention capabilities of buildings. In this paper, seismic simulation analyses of a steel-reinforced concrete high-rise building located in the Tokyo Bay area is conducted based on the seismic record of the Tohoku earthquake. A nonlinear sway-rocking model is used in the analysis, and comparisons are drawn between the observed records and analytical results of the pre-shock, main shock and earthquake after 1 month. The analytical results correspond well with the seismic records, and the effect of the nonlinear nature of the main shock is retained in the building. This is an important consideration when conducting response evaluation. An ARX (auto-regressive exogenous) model is used to identify the first and second natural periods, and the damping ratios, of both the records and the analytical results. Although the first and second damping ratios are similar in value to the observed results, the second damping ratio is overestimated in the analytical results because of the stiffness damping model.